2005
DOI: 10.1177/0891988704273375
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study on the Relationship Between Symptomatology of Dementia and Levels of Subjective Burden and Depression Among Family Caregivers in Memory Clinic Patients

Abstract: The objective was to evaluate the course and severity of dementia-related symptoms and their relationship to caregivers' subjective burden and depression over time. Forty-five patients with dementia and their caregivers were followed over a period of 2 years. Patients' cognition, function, and behavioral/psychological symptoms were assessed by the Mini Mental State Examination, Syndrome Kurz Test, Geriatric Depression Screening scale, Instrumental Activities of Daily Living Scale, Physical Self Maintenance Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 45 publications
3
110
0
6
Order By: Relevance
“…Studies have also found that increased caregiver burden is associated with increased incidence of caregiver depression. 24 It is possible that that mental health is intimately related to both violent behavior and bodily pain in the present study. Further study is needed to evaluate the relationship between violent patient behavior and caregiver mental health.…”
Section: Discussionmentioning
confidence: 92%
“…Studies have also found that increased caregiver burden is associated with increased incidence of caregiver depression. 24 It is possible that that mental health is intimately related to both violent behavior and bodily pain in the present study. Further study is needed to evaluate the relationship between violent patient behavior and caregiver mental health.…”
Section: Discussionmentioning
confidence: 92%
“…Literatürde de hastaların bakımından sorumlu olan kişilerin daha çok ailedeki kadın bireylerin ve eşlerin olduğu belirtilmektedir. [19,[29][30][31][32] Kadınların bakım verme işlevine uygun gö-rülmesinin en önemli nedeni; genellikle toplumlar tarafından ev işleri ve aile ile ilgili işlerin kadının doğal işi olarak gö-rülmesi, kadınların kişilik özellikleri nedeni ile daha şefkatli, daha duyarlı davranmaları, yakın ve güçlü ilişki kurabilme becerilerine sahip olmaları ve erkeklere kıyasla bakım verme işlevinin zorlukları ile daha iyi baş edebilecekleri görüşü olabilir. Ayrıca elde edilen sonuç kadınların çoğunun ev hanımı konumunda, düzenli işlerinin ve ekonomik gelirlerinin olmaması, farklı sosyal ortamlarda ve farklı rollerde bulunma olanağının kısıtlanması ve sosyal desteklerinin yetersiz olmasıyla ilgili olabileceğini düşündürmektedir.…”
Section: Discussionunclassified
“…Reasons for exclusion can be seen in Figure 1. The 40 included studies were quantitative, mainly cross-sectional with two longitudinal studies (Berger et al, 2005;Johnson et al, 2013), 21 studies were graded as high quality, and 19 as medium quality. A brief summary of the demographic data of the studies is provided in Table S1, along with a description of the measures used, quality score, and the main findings.…”
Section: Resultsmentioning
confidence: 99%